1998
DOI: 10.1111/j.1349-7006.1998.tb00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Phase Tumor Accumulation of Macromolecules: A Great Difference in Clearance Rate between Tumor and Normal Tissues

Abstract: The objective of this study was to investigate the molecular weight (MW) and time-dependence of the phenomenon termed "the enhanced permeability and retention" (EPR) effect in solid tumor, in particular to determine and define the early phase accumulation of macromolecules in tumor and normal tissues and the relationship between blood concentration and tissue clearance. As a model, radioiodinated N-(2-hydroxypropyl)methacrylamide (HPMA) copolymers of MW ranging from 4.5 K to 800 K were administered i.v. to mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
271
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 422 publications
(277 citation statements)
references
References 29 publications
5
271
0
1
Order By: Relevance
“…Smaller tumours exhibit the highest concentration of polymer-drug. Using HPMA copolymer fractions in the range 10 000-800 000 Da as probes (Seymour et al 1995, Noguchi et al 1998, we found that tumour uptake of polymers (usual molecular diameter 5-20 nm) had broad size tolerance and good intratumoural penetration compared with that reported for liposomes and nanoparticles. Conjugates have also been synthesised to contain ligands that might promote receptor-mediated targeting (including antibodies, peptides and saccharides) (reviewed in Duncan 2005a,b).…”
Section: Polymer-drug Conjugates: Rationale For Designmentioning
confidence: 83%
“…Smaller tumours exhibit the highest concentration of polymer-drug. Using HPMA copolymer fractions in the range 10 000-800 000 Da as probes (Seymour et al 1995, Noguchi et al 1998, we found that tumour uptake of polymers (usual molecular diameter 5-20 nm) had broad size tolerance and good intratumoural penetration compared with that reported for liposomes and nanoparticles. Conjugates have also been synthesised to contain ligands that might promote receptor-mediated targeting (including antibodies, peptides and saccharides) (reviewed in Duncan 2005a,b).…”
Section: Polymer-drug Conjugates: Rationale For Designmentioning
confidence: 83%
“…Furthermore, small molecules such as 5-FU are rapidly cleared from tumors in spite of the increased initial delivery by the enhanced perfusion and permeability of tumor vasculatures. [29][30][31] On the other hand, HT improved the targeting of 131 I-A7, a large molecule, by the phenomenon of so-called "enhanced permeability and retention (EPR)." [29][30][31] Bone marrow suppression is a major toxicity of RIT.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] On the other hand, HT improved the targeting of 131 I-A7, a large molecule, by the phenomenon of so-called "enhanced permeability and retention (EPR)." [29][30][31] Bone marrow suppression is a major toxicity of RIT. We found in previous studies that the combination of 5-FU slightly increased the myelotoxicity of RIT at its MTD dose, but cell counts recovered similarly to that in the single-modal RIT 21) and local HT did not affect the toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…These polymers have been developed in the basis of the achieved tumor-specific targeting by the enhanced permeability and retention effect (Ducan et al, 2005;Matsumura et al, 1986). This increasing tumor retention has been observed and attributed to the better extravasation in the blood vessel of macromolecules and the absence of their drainage release (Noguchi Y et al, 1998;Seymour et al, 1995). HPMA copolymer conjugate with chemotherapeutic agents as doxorubicin has shown high retention and efficacy toward tumors without side effects (Ducan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%